Morphological and functional parameters of the heart and vessels in patients with type 2 diabetes mellitus and cardiovascular autonomic neuropathy - Irina Arkad'evna Bondar'; Alexander Aristarkhovich Demin; Olesya Yur'evna Shabel'nikova (Сахарный диабет)
Objective. To evaluate morphological and functional parameters of the heart and vessels in patients with type 2 diabetes mellitus (DM2) and diabetic cardiovascular autonomic neuropathy (CAN). Materials and methods. A total of 139 patients with DM2 and hypertension (mean age: 53.1?4.9 years; mean duration of hypertension: 9.7?7.8 years) were included in this study. Based on cardiovascular autonomic function test results (electrocardiography, heart rate variability) patients were divided into 2 groups as follows: Group 1 included 40 patients without CAN and Group 2 included 99 patients with CAN. The control group comprised 30 patients with hypertension and normal carbohydrate metabolism (mean age: 53.1?6.0 years; mean duration of hypertension: 10.9?8.5 years). All patients underwent ultrasonography of the heart and common carotid artery. Results. Group 2 patients showed a significant decrease in maximal transmitral flow velocity during early diastolic filling (0.61?0.12 m/s) and a decrease in maximal transmitral flow velocity during late diastolic filling (0.65?0.11 m/s) compared with Group 1 patients (0.66?0.09 m/s and 0.69?0.09 m/s, respectively, р